Genistein alters coagulation gene expression in ovariectomised rats treated with phytoestrogens - Norris, Lucy; O'Leary, John; Kelly, Lynne (Elsevier, 2010)
Recent data has shown that hormone therapy (HT) increases the risk of cardiovascular and thromboembolic disease, particularly in users of oral HT. Phytoestrogens are popular alternatives to oestrogen therapy; however, their effects on cardiovascular risk are unknown. We investigated the effect of the phytoestrogen, genistein on the expression of genes and proteins from the haemostatic system in the liver in an ovariectomised rat model. Fifty-nine virgin female Sprague-Dawley rats were fed with soy-free chow supplemented with 17? estradiol (E2) (daily uptake 0.19 or 0.75 mg/kg body weight), or genistein (daily uptake 6 or 60 mg/kg body weight), for three months and compared to soy-free control rats. Gene expression of prothrombin, factor VII, fibrinogen alpha and fibrinogen beta was increased with E2 and genistein compared to the soy-free control group (p<0.001). Genistein increased factor VII significantly more than E2 (p<0.005). Plasminogen mRNA was increased in both treatment groups compared to the soy-free control, with genistein expression significantly higher than E2 (p<0.001). Tissue plasminogen inhibitor (tPA), plasminogen activator inhibitor-1 (PAI-1) and C-reactive protein (CRP) expression were also increased in both groups relative the soy-free control. Results of protein analysis largely concurred with those of the mRNA. Oestrogen receptor ? (ER?) was undetected while oestrogen receptor ? (ER?) was detected in each sample group. Genistein can increase the expression of coagulation and fibrinolytic genes. This effect was similar and in some cases higher than 17? estradiol. These results suggest that genistein may not be neutral with respect to the haemostatic system.
Thrombosis Research
7th Internation Conference on Thrombosis & Hemostatis Issues in Cancer,
PUBLISHED
Bergamot Italy
Keywords: Cardiac and Cardiovascular systems; Haemostasis; phytoestrogen; menopause; thrombosis; Cancer; Genes & Society